AB0372 Effect of Certolizumab Pegol on Workplace and Household Productivity in US Patients with Rheumatoid Arthritis with or without Prior Anti-Tumor Necrosis Factor Exposure: Results from the PREDICT Study. (10th June 2014) - Kavanaugh, A.; Mease, P.J.; Strand, V.; Purcaru, O.; Curtis, J.R.
Abstract : Background: The PREDICT trial (NCT01255761 ) compared the patient-reported Routine Assessment of Patient Index Data (RAPID3) and the investigator-based Clinical Disease Activity Index (CDAI) tools in US rheumatoid arthritis (RA) patients (pts) receiving certolizumab pegol (CZP). 1, 2 The validated RA-specific Work Productivity Survey (WPS) 3 was used to assess the impact of arthritis on pt productivity within and outside the home over the previous month. Objectives: To investigate the effect of CZP on workplace and household productivity and social participation in US RA pts with and without prior anti-TNF exposure in the PREDICT trial. Methods: Pts received CZP standard dosing regimen (400mg at Wks 0, 2, 4 [loading dose], then 200mg Q2W). The impact of RA on workplace and household productivity and daily activities was assessed by the WPS (administered Q4W until Wk24 and Q8W afterwards), stratified by pts with and without prior anti-TNF exposure. Mean WPS responses (LOCF) in the full analysis set (FAS) are summarized descriptively over 52 wks. Results: 733 pts were randomized; over half (55.5%) were prior anti-TNF failures. At baseline (BL), 38.8% and 49.4% of pts with and without prior anti-TNF exposure were employed outside the home, respectively. A high burden of RA on workplace and household productivity and social participation at BL was reported in pts with and without prior anti-TNF exposure, with on average >6 working days (anti-TNF naïve pts: mean 1.1 work days missed and 4.9 days with reduced productivity/month; prior anti-TNF pts: mean 1.8 work days missed and 6.5 days with reduced productivity/month) and >14 days of household work affected per month because of RA (anti-TNF naïve pts: mean 7.5 household work days missed and 7.4 days with reduced productivity/month; prior anti-TNF pts: mean 9.6 household work days missed and 7.8 days with reduced productivity/month; Table). Improvements were observed as early as Wk4 in both prior anti-TNF and anti-TNF naïve pts and were maintained through to Wk52. By Wk4, employed pts reported reductions in workplace absenteeism and presenteeism, as well as in the level of RA interference with work productivity (Table). Substantial improvements over time in both prior anti-TNF and anti-TNF naïve pts were also observed in household productivity and social participation. Conclusions: In RA pts initiating CZP, there were similar improvements between those with and without prior anti-TNF exposure in workplace, household productivity and social participation. These improvements were observed as early as Wk4 and maintained through Wk52. References: Anderson J. Arthritis Care Res 2012; 64:640-647. Castrejόn I. Clin Exp Rheumatol 2012; 30:S50-55. Osterhaus J.T. Arth Res Ther 2009; 11:R73 Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: A. Kavanaugh Grant/research support: Abbott, Amgen, BMS, Pfizer, Roche, Janssen, UCB Pharma, P. Mease Grant/research support: (Abbott) AbbVie, Amgen, BiogenIdec, BMS, Celgene, Crescendo, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB Pharma, Vertex, Consultant for: (Abbott) AbbVie, Amgen, BiogenIdec, BMS, Celgene, Crescendo, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB Pharma, Vertex, Speakers bureau: (Abbott) AbbVie, Amgen, BiogenIdec, BMS, Crescendo, Genentech, Janssen, Lilly, Pfizer, UCB Pharma, V. Strand Consultant for: UCB Pharma, O. Purcaru Employee of: UCB Pharma, J. Curtis Grant/research support: Roche, Genentech, UCB Pharma, Janssen, CORRONA, Amgen, Pfizer, BMS, Crescendo, AbbVie, Consultant for: Roche, Genentech, UCB Pharma, Janssen, CORRONA, Amgen, Pfizer, BMS, Crescendo, AbbVie DOI: 10.1136/annrheumdis-2014-eular.2007